Partitioning water footprints of rice for assessing their implications in the face of climate change in Bangladesh - Islam, Md. Touhidul; Amin, M. G. Mostofa; Islam, Deen; Jahan, Nusrat; Rahman, Mostafijur (Paddy and water environment, 2024)
To improve rice yields while conserving water and minimizing environmental impact, a lysimeter experiment was conducted at Bangladesh Agricultural University’s field irrigation laboratory in Mymensingh. This study, spanning 2018–2020, aimed to measure the water footprint (WF) of the Aman-Boro-Aman rotation, considering green water footprint (GWF; rainwater) and blue water footprint (BWF; irrigation water), with a focus on climate change implications. Various irrigation methods, including rainfed and several interval-based irrigations (I9D–irrigation applied after nine days of ponded water disappearance, I6D, I3D, I3D + NP–I3D with no percolation allowed, and I1D), were evaluated. Results showed rainfed treatments had higher GWF (1155–1575 L/kg) due to reliance on inconsistent rainfall, while irrigated ones had lower GWF (375–1084 L/kg) but increased BWF, notably I1D with the highest BWF (2675 L/kg). This contrast highlights significant water usage differences among irrigation methods. The total water footprint (TWF) varied, with rainfed methods showing 1460–1960 L/kg and I1D the highest at 3603 L/kg. The consumptive water footprint ranged from 734 L/kg (I3D + NP) to 1097 L/kg (rainfed), indicating the efficiency of no-percolation strategies in water conservation. This also led to improved nutrient availability, resulting in higher plant height and rice yield. Seasonal variations in TWF were also observed, with the Aman season showing greater variability than the Boro season due to differences in rainfall and irrigation practices. The study underscores the importance of managing irrigation frequency, timing, and percolation for optimizing rice water footprints under changing climatic conditions.